Identification of Amino Acid Residues Responsible for the Selectivity of Tadalafil Binding to Two Closely Related Phosphodiesterases, PDE5 and PDE6 - Cahill, Karyn B. (American Society for Biochemistry and Molecular Biology, 2012)
The 11 families of the Class I cyclic nucleotide phosphodiesterases (PDEs) are critical for regulation of cyclic nucleotide signaling. PDE5 (important in regulating vascular smooth muscle contraction) and PDE6 (responsible for regulating visual transduction in vertebrate photoreceptors) are structurally similar but have several functional differences whose structural basis is poorly understood. Using evolutionary trace analysis and structural homology modeling in conjunction with site-directed mutagenesis, we have tested the hypothesis that class-specific differences between PDE5 and PDE6 account for the biochemical and pharmacological differences in the two enzyme families. Replacing human PDE5 residues in the M-loop region of the binding site for the PDE5-selective inhibitor tadalafil (Cialis®) with the corresponding class-specific cone PDE6 residues (P773E, I778V, E780L, F787W, E796V, D803P, L804M, N806D, I813L, S815K) reduces tadalafil binding affinity to levels characteristic of PDE6. These mutations fail to alter vardenafil (Levitra®) affinity for the active site. Class-specific differences in PDE5 versus cone PDE6 that contribute to the accelerated catalytic efficiency of PDE6 were identified but required heterologous expression of full-length PDE5 constructs. Introduction of PDE6 residues into the background of the PDE5 protein sequence often led to loss of catalytic activity and reduced protein solubility, supporting the idea that multiple structural elements of PDE6 are highly susceptible to misfolding during heterologous expression. This work validates the use of PDE5 as a template to identify functional differences between PDE5 and PDE6 that will accelerate efforts to develop the next generation of PDE5-selective inhibitors with fewer adverse side effects resulting from PDE6 inhibition.